Integrating Repetitive Reading with Service-Learning in Ameliorating Critical Reading at a Private Islamic Junior High School - Idami, Zahratul; Nazaruddin, Nazaruddin; Wati, Shafrida; Kurniasy, Dessy; Febrian, Fadly (LSM Catimore dan Sahabat, 2024)
The Community Service Programme carried out by lecturers and students of the English Language Education Study Programme, Tarbiyah and Teacher Training Faculty of IAIN Langsa aimed to improve the English language skills of the community in the environment around the campus. This activity is carried out in the form of training to find the needs of the participants. In this activity, the intended participants were students of MTS Swasta An-Nur Kota Langsa grade VII that consisted of 11 students. The methods used in this activity included repetitive reading methods with a communicative approach through service-learning activities. The results of this programme showed a significant improvement in the critical reading skills of English narrative text as evidenced by the results of the score analysis with SPSS. The success of this programme not only has a positive impact on the participants, but also provides practical experience for students in applying English learning theory in the field, as well as strengthening the role of lecturers as community servants. The implementation of this programme reflects the institution's commitment to supporting sustainable educational development and contributing to improving the quality of human resources in the community.